Մոդելավորման մեթոդի կիրառման հնարավորությունները սոցիոլոգիական ուսումնասիրություններում - Վարդանյան Եվգինե (Bulletin of Yerevan University G: Economics, 2017)
Modeling was considered to be one of the famous methods, which is effectively used in natural sciences. Now it is also being actively implemented in sociological researches. The article is devoted to the study the opportunities of implementation of modeling in sociology and highlighting the main characteristics of that research method.